Efficient Synthesis of Diverse 5-Thio- or 5-Selenotriazoles: One-Pot Multicomponent Reaction from Elemental Sulfur or Selenium - Zhang, Lin-Lin; Li, Ya-Ting; Gao, Ting; Guo, Sha-Sha; Yang, Bei; Meng, Zi-Hui; Dai, Qi-Pu; Xu, Zhi-Bin; Wu, Qin-Pei (Synthesis, 2019)
A sequential multistep reaction toward 5-thio- or 5-selenotriazoles has been established by generation of both copper(I) triazolides and sulfenylating or selenylating agents in situ, starting from elemental sulfur or selenium. This reaction features mild conditions, readily available and broad-scope substrates, good functional group compatibility, high efficiency and regioselectivity, easy operation, and ligand-free CuI.
Keywords: sulfur; triazole; copper iodide; selenium; multicomponent reaction